2012
DOI: 10.1186/1472-6963-12-395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of case management in community aged care on client and carer outcomes: a systematic review of randomized trials and comparative observational studies

Abstract: BackgroundCase management has been applied in community aged care to meet frail older people’s holistic needs and promote cost-effectiveness. This systematic review aims to evaluate the effects of case management in community aged care on client and carer outcomes.MethodsWe searched Web of Science, Scopus, Medline, CINAHL (EBSCO) and PsycINFO (CSA) from inception to 2011 July. Inclusion criteria were: no restriction on date, English language, community-dwelling older people and/or carers, case management in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 38 publications
(54 reference statements)
4
103
1
1
Order By: Relevance
“…A number of studies lack blind assessment and intention-to-treat analysis. This is consistent with research by You et al (2012), which found that information about blind assessment and intention-totreat analysis was commonly missing in most studies. However, in some of the included studies with healthy volunteers from the general population, where measures were all selfassessed, these criteria were not applicable.…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies lack blind assessment and intention-to-treat analysis. This is consistent with research by You et al (2012), which found that information about blind assessment and intention-totreat analysis was commonly missing in most studies. However, in some of the included studies with healthy volunteers from the general population, where measures were all selfassessed, these criteria were not applicable.…”
Section: Discussionsupporting
confidence: 92%
“…These conclusions prove the usefulness of our qualitative inductive analysis of the effects of the implementation of the case management service in revealing factors that were not necessarily foreseen and could not be evaluated by an instrumental evaluation of care satisfaction or a randomized control trials that focus on the reduction of unplanned hospitalization, psychological well-being or unmet service need [31]. …”
Section: Discussionmentioning
confidence: 90%
“…Care managers may come from a variety of professional backgrounds, including nursing, but in this role they are employed as aged care professionals, rather than nurses. The care manager's role involves assessing clients' support needs and organizing personal care services such as housecleaning, medical appointments, physical care, shopping, meal delivery, and transport [13,27]. Care managers regularly visit clients at home.…”
Section: Technology-supported Aged Carementioning
confidence: 99%